Removal of heavy metals from bauxite residue using Gracilaria Sp. adsorbent - 610633 Edward Hingha Foday Junior, 1988- , author; Mohd. Fadhil Md. Din supervisor 283389; 640761 Shreeshivadasan Chelliapan, supervisor; 513808 Shazwin Mat Taib, supervisor; 507563 Faculty of Engineering (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Sarjana Kejuruteraan (Alam Sekitar) - Universiti Teknologi Malaysia, 2018